(untitled) (Aporte Santiaguino, 2022)
The objective of this research is to identify and determine the presence of PCBs in the Callejón de Huaylas area and the impacts they may cause on health and the environment. For this, the guides and manuals for the identification and environmental management of stocks of said PCBs have been taken into account, as well as the standardized methods and guidelines of the UNEP. As a result of the evaluations, it has been possible to determine the existence of PCBs in the dielectric oil of the transformer located in the district of Ticapampa, which was sampled and analyzed, finding Askarel or Aroclor in its composition, due to its conservation and age of the team; this confirming the existence of said chemical products in our environment. The investigation concluded that, in the case of health impacts, the workers who had direct contact with the equipment, do not have PPE, do not have a medical control, or record of it; claiming to have health problems. Regarding the impact on the environment, the operators state that the disposal of the waste is not adequate; on the contrary, they are disposed of together with household waste; in addition to burning them, generating air pollution.